USING A GAPS MODEL IN EXPLAINING THE DARK SIDE OF CUSTOMER RELATIONSHIP MANAGEMENT ON LUXURY HOTEL - Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2020)
A luxury hotel does not automatically embrace low standard of service from customers. This paper is an attempt to understand the service quality in the hotel industry's luxury segment with gaps model. The author states that the gaps model is a valuable tool for partially exposing the dark side. There's more on the dark side, including privacy concerns, consumers' inability on establish a relationship with the service provider and the customer's shifting tastes and preferences. One luxury hotel (synchronous as an R-C hotel) was chosen in this study, and the research questions were answered in the industry as a whole using R-C hotel as a classic example of superior customer service efficiency. There has been mention of some easy steps to raising the dark side, which answer the third and last research issue.